2006
DOI: 10.1111/j.1538-7836.2006.02089.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet hyperreactivity generalizes to multiple forms of stimulation

Abstract: Summary. Background: Although platelet hyperreactivity constitutes an important cardiovascular risk factor, standardized methods for its measurement are lacking. We recently reported that aggregometry using a submaximal concentration of epinephrine identifies individuals with in vitro platelet hyperreactivity; this hyperreactivity was reproducible on multiple occasions over long periods of time. Objective and methods: To better understand this aberrant reactivity, we studied in a large group of subjects (n ¼ 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 33 publications
(50 reference statements)
5
66
0
2
Order By: Relevance
“…[2][3][4][5][6][7][8] Interestingly the level of responsiveness within an individual is remarkably consistent over time, regardless of agonist, or function outcome measure. [2][3][4][8][9][10] This, coupled with evidence from studies in siblings, 11 twins, 12 and in families with a history of premature coronary artery disease (CAD), 13 suggests a high level of heritability of platelet response.…”
Section: Introductionmentioning
confidence: 94%
“…[2][3][4][5][6][7][8] Interestingly the level of responsiveness within an individual is remarkably consistent over time, regardless of agonist, or function outcome measure. [2][3][4][8][9][10] This, coupled with evidence from studies in siblings, 11 twins, 12 and in families with a history of premature coronary artery disease (CAD), 13 suggests a high level of heritability of platelet response.…”
Section: Introductionmentioning
confidence: 94%
“…The 1780AA genotype was associated with a shorter CT (ie, platelet hyperreactivity). Even though the SNP designations are different in Yabe et el 29 and Yee et al, 6 it is probable that these represent the same SNPs because the flanking sequence of the major allele in each case (TTTAAA) represents a DraI restriction site. According to the current dbSNP database (Build 131), this polymorphism is located at chr10:112,839,580 but has not been named.…”
Section: Candidate Gene Association Based On Ltamentioning
confidence: 99%
“…Several assays have been selected that fulfill these criteria, including light transmission aggregometry (LTA), 6 the Platelet Function Analyzer-100 (PFA-100; Siemens Diagnostics), 44 and the measurement of platelet activation events by flow cytometry, 2 but each is used in association studies under carefully considered conditions that may not be identical to those used in the routine clinical laboratory.…”
Section: Candidate Gene Association Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the considerable interindividual and intraindividual variation in response to various agonists in a healthy population, it was hypothesized that subjects with maximal aggregation induced by low agonist concentrations may exhibit hyperreactive platelet phenotype that is associated with an increased risk for thrombotic complications. 17,18 Faraday et al demonstrated that heritable factors indirectly related to COX-1 contribute prominently to variability in residual platelet function after aspirin therapy in 1880 asymptomatic subjects from families with premature coronary heart disease. They showed that the same factors that contribute to the variability in indirect COX-1 pathways (described later) during aspirin therapy also contribute to the variability before aspirin therapy.…”
Section: Variability In Platelet Response To Agonists and Its Relatiomentioning
confidence: 99%